Strain echocardiography improves prediction of arrhythmic events in ischemic and non-ischemic dilated cardiomyopathy. (1st November 2021) - Melichova, Daniela; Nguyen, Thuy M.; Salte, Ivar M.; Klaeboe, Lars Gunnar; Sjøli, Benthe; Karlsen, Sigve; Dahlslett, Thomas; Leren, Ida S.; Edvardsen, Thor; Brunvand, Harald; Haugaa, Kristina H.
Abstract: Background: Recent evidence suggests that an implantable cardioverter defibrillator (ICD) in non-ischemic cardiomyopathy (NICM) may not offer mortality benefit. We aimed to investigate if etiology of heart failure and strain echocardiography can improve risk stratification of life threatening ventricular arrhythmia (VA) in heart failure patients. Methods: This prospective multi-center follow-up study consecutively included NICM and ischemic cardiomyopathy (ICM) patients with left ventricular ejection fraction (LVEF) <40%. We assessed LVEF, global longitudinal strain (GLS) and mechanical dispersion (MD) by echocardiography. Ventricular arrhythmia was defined as sustained ventricular tachycardia, sudden cardiac death or appropriate shock from an ICD. Results: We included 290 patients (67 ± 13 years old, 74% males, 207(71%) ICM). During 22 ± 12 months follow up, VA occurred in 32(11%) patients. MD and GLS were both markers of VA in patients with ICM and NICM, whereas LVEF was not ( p  = 0.14). MD independently predicted VA (HR: 1.19; 95% CI 1.08–1.32, p  = 0.001), with excellent arrhythmia free survival in patients with MD <70 ms (Log rank p  < 0.001). Patients with NICM and MD <70 ms had the lowest VA incidence with an event rate of 3%/year, while patients with ICM and MD >70 ms had highest VA incidence with an event rate of 16%/year. Conclusion: Patients with NICM and normal MD had low arrhythmic event rate, comparable to the general population. Patients with ICM and MD >70 ms had the highest risk of VA. Combining heart failure etiology and strain echocardiography may classify heart failure patients in low, intermediate and high risk of VA and thereby aid ICD decision strategies. Highlights: Risk stratification by strain echocardiography may add important information when considering a primary prophylactic ICD. Non-ischemic dilated cardiomyopathy with low mechanical dispersion had an arrhythmic rate close to the general population. Ejection fraction < 40% and mechanical dispersion >70 ms indicates monitoring for arrhythmias irrespective of etiology.